Persepsi Bentuk Penugasan Mata Pelajaran Geografi dalam Penerapan Kurikulum Merdeka - Mushoddik; Alwin; Citra Adelia Daratista (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Education reflects society's ability to produce competent individuals who contribute positively. As times evolve, the education system undergoes transformation to meet modern era demands. Technological and informational advancements influence students' knowledge, skills, and social aspects in completing tasks, encouraging them to be more adaptive. Indonesia has implemented various curricula, with the Merdeka Curriculum being the latest. This curriculum is expected to deepen conceptual understanding and strengthen student competencies in the dynamic global era. This study analyzes the perceptions of 10th-grade public high school students in Tapos District, Depok, regarding geography subject assignment forms in the Merdeka Curriculum. Using a quantitative descriptive approach with a questionnaire as the main instrument, this study finds that the majority of students (64%) have a good perception of these assignment forms. The implementation of the Merdeka Curriculum shows variations in assignment forms, including print-based technology, audio-visual, computer, and their combinations. In conclusion, students have a positive understanding and view of various geography assignment forms in the Merdeka Curriculum.